Application of Sorbent Extraction for Preconcentration/Separation of Trace Amounts of Cadmium(II), Silver(I), Gold(II) and Lead(II) from Metallic Zinc Samples and Their Determinations by Atomic Absorption Spectrometry - Uzun, A.; Soylak, M.; Elci, L.; Dogan , M. (Asian Journal of Chemistry, 2010)
The determinations of cadmium(II), silver(I), gold(II) and lead(II) in metallic zinc samples were performed using separation-preconcentration procedure on an Amberlite XAD-16 adsorption resin column. Cadmium, silver, gold and lead were quantitatively recovered and separated from a solution containing 1 M HCl and 0.3 M NaI. Effects of the matrix have been investigated. The recoveries of interesting elements were found to be in the range of 95–103% through the use of proposed method. The procedure was successfully applied to the determination of trace impurities in four metallic zinc samples (recoveries > 95%, relative standard deviations < 10).